Effects of Global Pandemic on Stock Liquidity in the Nigerian Stock Exchange - Fakunmoju, Segun; Jegede, C. A.; Oluchi, A. (EuroEconomica, 2022)
Stock liquidity plays important role in investors’ participation in any nation’s stock market. The global pandemic shock created market illiquidity especially among developing stock market like Nigerian stock market. However, the emergence of global pandemic via COVID-19 pandemic triggered declined market turnover (stock liquidity) which in turn created lack of confidence among stock investors in Nigeria. This study therefore examined the effects of Global pandemic on stock liquidity in the Nigerian stock market using stock turnover and COVID-19 pandemic as measure for stock market liquidity and global pandemic. The study employed expost facto research design using weekly data of both corona-virus pandemic and stock market turnover within the period of March, 2019 to February, 2022. The study employed Exponential GARCH (EGARCH) model and found a considerable negative consequence of Global Pandemic (Covid-19) on stock liquidity, implying that corona-virus pandemic has brought bad information (bad news) which deteriorate the liquidity in the stock exchange market. The study concluded that COVID-19 pandemic shock reduces stock liquidity in Nigerian stock exchange market. The study however recommended that government should put in place more palliative policies such as tax incentive and lowest interest rate on loan to individual and institutional investors which will cushion effect of COVID-19 pandemic and increase investors’ participation in the Nigerian stock market. Also, Nigeria stock market regulators should put in place sound measures that will enhance availability of stock information so as to arouse the interest more and new investors to the Nigerian Stock Market.